The model Happy and Integral Schools in the improvement of quality in an Educational NETWORK of Ventanilla - Rodríguez Melgar, Silvia Vanessa (2018)
Study of hypothetical deductive explanatory, whose objective was to demonstrate how the Model Happy and Integrated Schools - Model (EFI) contributed to the improvement of the quality of a NETWORK of four Educational Institutions of the district of Ventanilla, for which observation cards were applied of classroom, institutional climate surveys; and scale of observation of student treatment; 623 children participated in the study, 38 teachers; 4 directors and 151 parents; the conclusion refers to an improvement of 47% in the criteria of equity and inclusivity in these institutions, 25% in the improvement of multidisciplinary management, 17% in the improvement of the institutional climate; and in 50% of the improvement of the participation and agreement of the educational community of these schools.